Prognosis of Acute Pancreatitis: It's a Challenge - José de Jesús Urbina Cabello; Morelos Adolfo García Sánchez; Sergio Alberto García Sánchez; Estefania Rojas González; José Francisco Centellano Cortés; Juana Karina Aguirre Maldonado; Juan Carlos Hernández Ordóñez; Brenda Lizeth Herrera Gómez Tagle; Edwin Díaz Pérez; Luis Octavio Victoria García; Oscar Gregorio Ramírez Gamboa (British Journal of Healthcare and Medical Research, 2026)
Introduction: acute pancreatitis is a mild to very severe inflammation of the pancreas, presenting a broad clinical spectrum and significant risk of morbidity and mortality. Objective: to determine whether base and lactate deficiency are predictive factors in patients with severe acute pancreatitis. Method: retrospective, longitudinal, observational and descriptive study in patients with acute pancreatitis in the Surgery Department of a second-level care hospital. Results: 65 patients with acute pancreatitis: 39 women 60%, 26 men 40%. Higher incidence of age from 20 to 29 years. Of which with severe pancreatitis: 23 (35%) and mild: 42 (65). The excess of base predicting severity with BISAP scale/risk of organ failure with Marshall scale yields sensitivity of 44.4% and a specificity of 75.9% and 38.9% and 75.9% respectively, so 55.6% and 61.1% of patients with acute pancreatitis. Discussion: currently, there are multiple scoring systems to assess the severity of acute pancreatitis. The revised Atlanta classification is a clinically proven, widely used, and universally accepted classification system. To identify the severity of acute pancreatitis early, with stratification of the patient's risk on admission, distinguishing between mild and potentially fatal forms. Allowing rapid intervention with aggressive therapies in severe cases, reducing complications and mortality. Conclusions: markers such as baseline deficit and lactate are predictive factors in patients with acute pancreatitis, they have been shown to be non-specific, but with a certain degree of sensitivity determining the severity of the patient.